ARCHEOLOGY OF ANCIENT AND MEDIEVAL PERIOD OF CENTRAL ASIA - Mahfuza Eshquvvatova (Western European Studies, 2024)
General information about the ancient and medieval period of Central Asia and historians conducting research on these periods, as well as brief information about the monuments and settlements of the Stone Age and Medieval period of Central Asia.
Keywords: Stone Age; Usturshona; Paleolithic; Mesolithic